Impact of Corporate Social Responsibility on Children's Education Program of Suku Anak Dalam assisted by PT. Pertamina Hulu Energi Jambi Merang - Fatika Hastigerina Ananda; Tefy Nofadila (GoAcademica Research & Publishing, 2023)
This study aims to measure the impact of the CSR program assisted by PT. Pertamina Hulu Energi (PHE) Jambi Merang on the education sector for children of Suku Anak Dalam (SAD) through Social Return on Investment analysis. This research was a descriptive quantitative approach that used primary and secondary data sources. Primary data was collected through observation and interviews, while secondary data was collected through a literature study. Based on the results of the SROI calculation for the program, the conclusion was the social investment designed for this program was feasible indicated by the SROI score higher than one or giving positive SROI score during program implementation. According to the SROI calculation analysis results, the program has produced benefits greater than the program costs. Moreover, the scope of the program needs to be extended to increase the number of benefit receivers.